2017
DOI: 10.2147/ijn.s132434
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal curcumin and its application in cancer

Abstract: Curcumin (CUR) is a yellow polyphenolic compound derived from the plant turmeric. It is widely used to treat many types of diseases, including cancers such as those of lung, cervices, prostate, breast, bone and liver. However, its effectiveness has been limited due to poor aqueous solubility, low bioavailability and rapid metabolism and systemic elimination. To solve these problems, researchers have tried to explore novel drug delivery systems such as liposomes, solid dispersion, microemulsion, micelles, nanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
208
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(227 citation statements)
references
References 109 publications
2
208
0
1
Order By: Relevance
“…Wet grinding process could partly break down curcumin crystals also and turn them into the amorphous state. [8] Therefore, in the present study, the crystallinity of starch as well as curcumin had been affected by the grinding process and the XRD pattern of OSA starch loaded nanocurcumin was mostly amorphous. It was also reported that the solubility of curcumin in water was due to the www.advancedsciencenews.com www.starch-journal.com change of curcumin from its crystalline form to amorphous form when curcumin was wet milled with OSA starch.…”
Section: Xrd Analysismentioning
confidence: 66%
See 3 more Smart Citations
“…Wet grinding process could partly break down curcumin crystals also and turn them into the amorphous state. [8] Therefore, in the present study, the crystallinity of starch as well as curcumin had been affected by the grinding process and the XRD pattern of OSA starch loaded nanocurcumin was mostly amorphous. It was also reported that the solubility of curcumin in water was due to the www.advancedsciencenews.com www.starch-journal.com change of curcumin from its crystalline form to amorphous form when curcumin was wet milled with OSA starch.…”
Section: Xrd Analysismentioning
confidence: 66%
“…Amylopectin molecules are more susceptible to degradation because of their rigid double helical crystallites than the more flexible amylose molecules. Wet grinding process could partly break down curcumin crystals also and turn them into the amorphous state . Therefore, in the present study, the crystallinity of starch as well as curcumin had been affected by the grinding process and the XRD pattern of OSA starch loaded nanocurcumin was mostly amorphous.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, it downregulates the expression of differentiated embryochondrocyte expressed gene 1 (DEC1) and hypoxia-inducible factor-1-α (HIF-1α) [33][34][35][36].…”
Section: Curcuma Longamentioning
confidence: 99%